Juridical Analysis of the Implementation of Restorative Justice in the Legal Process of Fraud and Embezzlement Criminal Acts - Geri, Geri Tanduk Manurun; Hendri Jayadi Pandiangan; Armunanto Hutahaean (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
This article investigates the juridical implications of applying restorative justice in the resolution of fraud and embezzlement cases in Indonesia. The conventional criminal justice system, often characterized by its retributive orientation, is increasingly challenged for its inability to offer meaningful restitution to victims and lasting resolutions to offenders. Restorative justice presents an alternative paradigm, aiming to restore social harmony by actively involving victims, offenders, law enforcement, and communities in consensual conflict resolution. This study adopts a normative juridical research approach supported by case analysis of the Indonesian National Police's application of restorative justice, specifically referencing Police Report No. LP/B/0664/XI/2021/BARESKRIM POLRI. Legal and institutional frameworks including the Indonesian Penal Code, Law No. 11 of 2012 on the Juvenile Criminal Justice System, and Regulation of the Attorney General No. 15 of 2020 serve as the core references. The findings highlight that restorative justice can effectively resolve minor criminal offenses such as fraud and embezzlement when certain material and formal conditions are met, including community consent and documented mutual agreement between involved parties. This research argues that the restorative approach is not only legally viable but also ethically and socially more responsive to the needs of victims and communities. The study recommends broader institutional adoption and harmonization of restorative principles across judicial bodies to ensure sustainable justice reform. Keywords: Restorative Justice, Criminal Law Reform, Fraud, Embezzlement, Indonesia